Machining Properties of Two Lesser Used Timber from West Papua - Wahyudi S Pono; Muhamad Makrus; Antonius EB Susilo (Masyarakat Peneliti Kayu Indonesia, 2014)
Machining properties of wood play important roles in wood-working processes and will determine quality of end-wood products. There are several less-used species of wood with superior properties and could be promoted as commercial timber. This research was designed to explore the machining properties of two less-used spesies from West Papua of, watergum (Syzygium sp) and simpur (Dillenia sp). Varibles used to evaluate the machining properties are planning, sanding, boring, mortising, and turning. A modified-ASTM D 1666-64 was used to investigate this experiment. The results indicated that water gum was classified to the first class of machining properties (very good) having free defects of 83.70%, while simpur belongs to the second class (good) with free defects of 72.55%. These wood species are comparable with matoa and could be used as substituent timber. According to their density, these two wood species were suitable for general construction, housing material and furniture products. Both species are highly being recommended for customer preferences instead of the previously favourable timbers.Key words: machining properties, less-used species, simpur, water gum